Expanded graphite worm powder loaded Cu-In-Fe three-metal catalyst as well as preparation and application thereof
By using expanded graphite worm powder-supported Cu-In-Fe trimetal catalyst in acetylene semihydrogenation reaction, the problems of low activity and poor stability of Cu-based catalysts are solved, the acetylene conversion rate and ethylene selectivity are improved, and the lower acetylene conversion rate and ethylene selectivity are achieved. Reaction temperature and high stability, suitable for industrial applications.
Patent Information
- Application Number
- CN202411387428.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-02
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-02
AI Technical Summary
The existing Cu-based catalysts have low catalytic activity and poor stability in the acetylene semihydrogenation reaction, resulting in low acetylene conversion and ethylene selectivity, and are prone to problems such as C-C polymerization to form green oil.
Cu-In-Fe 3 was prepared by using expanded graphite worm powder as a carrier. Copper salt, indium salt and iron salt were loaded onto expanded graphite worm powder by wet impregnation, and calcined at high temperature in an inert gas environment and reduced in hydrogen. Metal catalyst adjusts the geometry and electronic structure of Cu nanoparticles to improve catalytic performance.
It improves the stability and activity of the catalyst, enhances the conversion rate of acetylene and the selectivity of ethylene, reduces the reaction temperature, and is relatively cheap, suitable for industrial applications.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of acetylene hydrogenation catalysts, and particularly relates to an expanded graphite worm powder-loaded Cu-In-Fe trimetallic catalyst, a preparation method thereof, and an application thereof in an acetylene semi-hydrogenation reaction. Technical Background
[0002] Ethylene is one of the most important chemicals in the petrochemical industry and is usually obtained by cracking petroleum hydrocarbons with a small amount of acetylene as a by-product. Trace amounts of acetylene can poison ethylene polymerization catalysts and reduce the quality of polyethylene. Semi-hydrogenation of acetylene in ethylene-rich gas streams is a key step in the industrial production of polyethylene. An ideal catalyst should be able to convert acetylene into ethylene with high selectivity while preventing further hydrogenation of ethylene to ethane.
[0003] Cu-based catalysts have attracted widespread attention due to their high ethylene selectivity due to their strong acetylene adsorption capacity and weak ethylene adsorption capacity. However, they are weak in hydrogen dissociation ability, low catalytic activity, and prone to CC polymerization to form green oil, which leads to catalyst deactivation. Modifying the geometric or electronic structure of Cu-based catalysts and using the interaction between copper nanoparticles and additives and carriers to control the size, morphology and distribution of copper nanoparticles are the keys to improving the catalytic hydrogenation activity, selectivity and durability of copper-based catalysts. Although the use of traditional metal oxides (such as Al2O3, Ti2O3) as carriers can improve the dispersibility of Cu nanoparticles, it is still challenging to synthesize highly dispersed nanoparticles with uniform size through traditional methods.
[0004] Expanded graphite worm powder (EG) is a loose and porous worm-like substance obtained by intercalation, washing, drying and high-temperature expansion of natural graphite flakes. As a new functional carbon material, EG not only has the excellent properties of natural graphite itself, such as resistance to cold and heat, corrosion resistance, and self-lubrication, but also has the characteristics of softness, compression resilience, adsorption, ecological environment coordination, biocompatibility, and radiation resistance that natural graphite does not have. When exposed to high temperature, the expanded graphite can instantly expand 150 to 300 times in volume, changing from flake to worm-like, so that the structure is loose, porous and curved, the surface area is expanded, the surface energy is increased, the adsorption force of flake graphite is enhanced, and the worm-like graphite can be self-interlocked, which increases its softness, resilience and plasticity. Therefore, expanded graphite worm powder is particularly widely used in petroleum, chemical industry, atomic energy, electricity, and pharmaceuticals. With the progress of science and technology and the development of high technology, expanded graphite, a new engineering material, has gradually replaced certain metal materials and organic synthetic materials in high-tech fields such as high speed, corrosion resistance, wear resistance and energy saving.
[0005] Therefore, it is necessary to develop a preparation method for expanded graphite worm powder loaded with Cu-based trimetallic catalysts, adjust the geometric and electronic structure of Cu nanoparticles and produce a synergistic effect to improve the acetylene semi-hydrogenation catalytic performance of the catalyst.
[0006] Based on the above background, the present invention proposes an expanded graphite worm powder loaded with Cu-In-Fe trimetallic catalyst. Summary of the invention
[0007] The invention aims to provide an expanded graphite worm powder-loaded Cu-In-Fe trimetallic catalyst, a preparation method thereof and application thereof in an acetylene semi-hydrogenation reaction. The catalyst makes up for the shortcomings of acetylene semi-hydrogenation copper-based catalysts such as low catalytic activity and poor stability, and has the characteristics of simple preparation, good stability, high conversion rate, high selectivity and relatively low reaction temperature.
[0008] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:
[0009] In a first aspect, the present invention provides an expanded graphite worm powder (EG) loaded Cu-In-Fe trimetallic catalyst, wherein the catalyst is prepared by the following method using the expanded graphite worm powder as a carrier: copper salt, indium salt and iron salt are loaded onto the expanded graphite worm powder by wet impregnation to obtain a mixed sample, and then the mixed sample is placed in an inert gas environment and calcined at a high temperature to obtain a calcined product; and the obtained calcined product is reduced in a hydrogen atmosphere to obtain an expanded graphite worm powder loaded Cu-In-Fe trimetallic catalyst;
[0010] Among them, the feeding ratio of the copper salt, indium salt, iron salt and expanded graphite worm powder needs to make the expanded graphite worm powder load the Cu-In-Fe trimetallic catalyst with 1%-10% of the theoretical loading amount of copper, 0.1%-5% of indium, and 0.1%-2.5% of iron. The theoretical loading amount is calculated as the percentage of the mass of copper, indium and iron elements contained in the copper salt, indium salt and iron salt respectively to the mass of the expanded graphite worm powder.
[0011] Preferably, the theoretical loading amount of copper is 1%-5%, the theoretical loading amount of indium is 0.5%-2.5%, and the theoretical loading amount of iron is 0.5%-2%.
[0012] Preferably, the calcination temperature is 150-1200°C, more preferably 250-1000°C, further preferably 350-700°C; the calcination time is 1-8h, more preferably 2-6h.
[0013] Preferably, the reduction temperature is 200-600°C, more preferably 350-450°C; and the reduction time is 1-4h.
[0014] In a second aspect, the present invention provides a method for preparing the expanded graphite worm powder-loaded Cu-In-Fe trimetallic catalyst according to the first aspect, comprising the following steps:
[0015] (1) Weighing copper salt, indium salt and iron salt, dissolving them in deionized water, and stirring them thoroughly at room temperature to obtain a mixed solution; adding expanded graphite worm powder (EG) to the mixed solution, stirring the mixture at room temperature for 8-12 hours, and drying to obtain a mixed sample powder;
[0016] (2) placing the mixed sample powder obtained in step (1) in an inert gas environment and calcining it at high temperature to obtain a calcined product;
[0017] (3) reducing the calcined product obtained in step (2) in a hydrogen atmosphere to obtain a Cu-In-Fe trimetallic catalyst (Cu-In-Fe / EG) supported by expanded graphite worm powder.
[0018] Preferably, the copper salt in step (1) is selected from one or more of anhydrous or crystalline water-containing copper nitrate, copper sulfate, copper chloride, copper bromide, and copper acetate.
[0019] Preferably, the indium salt in step (1) is selected from one or more of indium chloride, indium sulfate, indium nitrate, indium perchlorate, and indium cyclopentadienyl.
[0020] Preferably, the iron salt in step (1) is selected from one or more of anhydrous and crystalline water-containing iron hydroxide, iron sulfate, iron sulfate, iron chloride, iron nitrate, and iron phthalocyanine.
[0021] Preferably, in step (1), the drying temperature is 60-120° C., more preferably 80-110° C.; and the drying time is 8-12 h.
[0022] Preferably, the inert gas in step (2) is one of nitrogen, argon and helium.
[0023] Preferably, the calcination temperature in step (2) is 150-1200° C., more preferably 250-1000° C., and further preferably 350-700° C.; the calcination time is 1-8 h, and more preferably 2-6 h.
[0024] Preferably, in step (3), the reduction temperature is 200-600°C, more preferably 350-450°C; and the reduction time is 1-4h.
[0025] The expanded graphite worm powder of the present invention can be prepared by the method reported in the existing literature. The present invention specifically recommends a method for preparing expanded graphite worm powder, comprising the following steps:
[0026] (a) adding graphite and an appropriate amount of concentrated sulfuric acid into a beaker, mixing, stirring at room temperature for ≥2h to obtain a mixture, adding potassium persulfate to the mixture, stirring evenly, and immediately moving into a water bath to obtain acidic expanded graphite; wherein, by mass, the graphite: potassium persulfate: concentrated sulfuric acid = 1:5-10:40-100, preferably 1:5-10:45-55;
[0027] (b) filtering the acidic expanded graphite obtained in step (1) in vacuum, washing it to neutrality, and drying it to obtain expanded graphite worm powder (EG). The preparation method of the expanded graphite worm powder is relatively mild.
[0028] Preferably, in step (a), the graphite is selected from one or more of dense crystalline graphite, flake graphite, and cryptocrystalline graphite.
[0029] Preferably, the water bath temperature in step (a) is 40-120° C., more preferably 60-100° C., and the water bath time is 1-20 min.
[0030] Preferably, the drying temperature in step (b) is 40-100° C. and the drying time is 3-8 h.
[0031] In a third aspect, the present invention provides an application of the expanded graphite worm powder loaded Cu-In-Fe trimetallic catalyst according to the first aspect in the semi-hydrogenation reaction of acetylene.
[0032] Preferably, the acetylene semi-hydrogenation reaction is specifically implemented as follows: a raw material gas containing acetylene and hydrogen is introduced into a fixed bed reactor filled with expanded graphite worm powder loaded with a Cu-In-Fe trimetallic catalyst to convert acetylene into ethylene.
[0033] As further preferred, the reaction conditions for acetylene semi-hydrogenation are: reaction temperature 80-250°C, more preferably 150-200°C, further preferably 150-180°C; reaction pressure 0.1 MPa.
[0034] In a specific embodiment of the present invention, the raw material gas containing acetylene and hydrogen is composed of acetylene, hydrogen, ethylene, and the balance of nitrogen, and the feed space velocity is 1000 to 20000 h -1 .
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] 1. The present invention utilizes expanded graphite worm powder to load the Cu-In-Fe trimetallic catalyst, thereby improving the structural stability of copper, reducing the loss of active components, and improving the stability of the catalyst;
[0037] 2. The expanded graphite worm powder loaded Cu-In-Fe trimetallic catalyst of the present invention has better catalytic activity than other copper-based catalysts;
[0038] 3. The present invention uses expanded graphite worm powder loaded with Cu-In-Fe trimetallic catalyst for acetylene semi-hydrogenation reaction. The high specific surface area of expanded graphite worm powder is conducive to the dispersion of metal elements, the adsorption of reactants, and the desorption of products, thereby improving the conversion rate of acetylene and the selectivity of ethylene;
[0039] 4. Compared with precious metal catalysts, the expanded graphite worm powder loaded Cu-In-Fe trimetallic catalyst described in the present invention is relatively cheap and suitable for industrial application.
[0040] In summary, the method for preparing the expanded graphite worm powder loaded Cu-In-Fe trimetallic catalyst described in the present invention greatly improves the stability, activity and selectivity of the catalyst compared with traditional copper-based catalysts, and has a good application prospect. DETAILED DESCRIPTION
[0041] The present invention is described below with specific examples. It is necessary to point out that the embodiments are only used to further illustrate the present invention, but cannot be understood as limiting the scope of protection of the present invention, and the present invention is not limited thereto in any way. Those skilled in the art in this field can make some non-essential improvements and adjustments based on the content of the above invention.
[0042] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained by conventional technical means or purchased commercially.
[0043] The present invention adopts an online gas chromatograph to analyze the acetylene hydrogenation product, and calculates the conversion rate of acetylene and the selectivity of ethylene through an area normalization method.
[0044] Example 1
[0045] 1) Add 10g of graphite and 500g of concentrated sulfuric acid to a beaker, mix, and stir at room temperature for 10h to obtain a mixture. Add 70g of potassium persulfate to the mixture, stir evenly, and immediately move into an 80°C water bath for 5min to obtain acidic expanded graphite. Filter the obtained acidic expanded graphite in a vacuum, wash it to neutrality, and dry it at 60°C for 5h to obtain expanded graphite worm powder (EG).
[0046] 2) Weigh 0.21g of anhydrous copper chloride, 0.1g of indium chloride and 0.145g of ferric chloride and dissolve them in deionized water, and stir them thoroughly at room temperature to obtain a mixed solution. Take 5g of expanded graphite worm powder and add it to the mixed solution, stir the mixture at room temperature for 10h, and dry it at 100℃ for 10h to obtain a mixed sample powder. The obtained mixed sample powder is placed in an argon environment and calcined at 600℃ for 4h to obtain a calcined product.
[0047] 3) 0.3 g of the calcined product was placed in a fixed bed reactor. Before the reaction, pure H2 was introduced for reduction at 400°C for 2 h at a reducing gas flow rate of 50 mL / min to obtain expanded graphite worm powder-loaded Cu-In-Fe trimetallic catalyst (Cu-In-Fe / EG);
[0048] 4) After reduction, acetylene mixed gas was introduced at a rate of 50 mL / min. The volume concentration of the acetylene mixed gas was: 0.33% acetylene, 3.3% hydrogen, 33% ethylene, and the balance nitrogen, with a total amount of 100%. -1 The hydrogenation reaction was carried out at a pressure of 0.1 MPa and 180°C. The peak areas of ethane, ethylene, acetylene and C4 were detected online by gas chromatography, and the conversion rate of acetylene and the selectivity of ethylene were calculated by the area normalization method.
[0049] Calculation based on chromatographic data showed that when the reaction reached stability, the acetylene conversion was 99.8% and the ethylene selectivity was 98.8%. After 350 hours of reaction, the acetylene conversion was 98.9% and the ethylene selectivity was 97.1%.
[0050] Comparative Example 1
[0051] 1) Weigh 0.21g of anhydrous copper chloride, 0.1g of indium chloride and 0.145g of ferric chloride and dissolve them in deionized water, and stir them thoroughly at room temperature to obtain a mixed solution. Take 5g of γ-alumina (325 mesh) and add it to the mixed solution, and stir the mixture at room temperature for 10h, and dry it at 100℃ for 10h to obtain a mixed sample powder. The obtained mixed sample powder is placed in an argon environment and calcined at 600℃ for 4h to obtain a calcined product.
[0052] 2) 0.3 g of the calcined product was placed in a fixed bed reactor, and before the reaction, pure H2 was introduced for reduction at 400°C for 2 h, with a reducing gas flow rate of 50 mL / min, to obtain a γ-alumina-supported Cu-In-Fe trimetallic catalyst (Cu-In-Fe / γ-Al2O3);
[0053] 4) After reduction, acetylene mixed gas was introduced at a rate of 50 mL / min. The volume concentration of the acetylene mixed gas was: 0.33% acetylene, 3.3% hydrogen, 33% ethylene, and the balance nitrogen, with a total amount of 100%.-1 The hydrogenation reaction was carried out at 0.1 MPa, pressure and 180°C. The peak areas of ethane, ethylene, acetylene and C4 were detected online by gas chromatography, and the conversion rate of acetylene and its selectivity for ethylene were calculated by area normalization method.
[0054] Calculation based on chromatographic data showed that when the reaction reached stability, the acetylene conversion was 95.6% and the ethylene selectivity was 90.8%. After 150 hours of reaction, the acetylene conversion was 91.2% and the ethylene selectivity was 67.1%.
[0055] Comparative Example 2
[0056] 1) Weigh 0.21g of anhydrous copper chloride, 0.1g of indium chloride and 0.145g of ferric chloride and dissolve them in deionized water, and stir them thoroughly at room temperature to obtain a mixed solution. Take 5g of titanium dioxide (325 mesh) and add it to the mixed solution, and stir the mixture at room temperature for 10h, and dry it at 100℃ for 10h to obtain a mixed sample powder. The obtained mixed sample powder is placed in an argon environment and calcined at 600℃ for 4h to obtain a calcined product.
[0057] 2) 0.3 g of the calcined product was placed in a fixed bed reactor, and before the reaction, pure H2 was introduced for reduction at 400°C for 2 h, with a reducing gas flow rate of 50 mL / min, to obtain a γ-alumina-supported Cu-In-Fe trimetallic catalyst (Cu-In-Fe / γ-Al2O3);
[0058] 4) After reduction, acetylene mixed gas was introduced at a rate of 50 mL / min. The volume concentration of the acetylene mixed gas was: 0.33% acetylene, 3.3% hydrogen, 33% ethylene, and the balance nitrogen, with a total amount of 100%. -1 The hydrogenation reaction was carried out at 0.1 MPa, pressure and 180°C. The peak areas of ethane, ethylene, acetylene and C4 were detected online by gas chromatography, and the conversion rate of acetylene and its selectivity for ethylene were calculated by area normalization method.
[0059] Calculation based on chromatographic data showed that when the reaction reached stability, the acetylene conversion was 94.9% and the ethylene selectivity was 91.1%. After 150 hours of reaction, the acetylene conversion was 90.2% and the ethylene selectivity was 69.7%.
[0060] Through Example 1 and Comparative Examples 1-2, it can be seen that the Cu-In-Fe trimetallic catalyst supported by expanded graphite worm powder is superior to the catalyst supported by γ-alumina and titanium dioxide.
[0061] Example 2
[0062] 1) Add 10g of graphite and 500g of concentrated sulfuric acid to a beaker, mix, and stir at room temperature for 10h to obtain a mixture. Add 70g of potassium persulfate to the mixture, stir evenly, and immediately move into an 80°C water bath for 5min to obtain acidic expanded graphite. Filter the obtained acidic expanded graphite in a vacuum, wash it to neutrality, and dry it at 60°C for 5h to obtain expanded graphite worm powder (EG).
[0063] 2) Weigh 0.295g of anhydrous copper nitrate, 0.131g of indium nitrate and 0.217g of ferric nitrate and dissolve them in deionized water, and stir them thoroughly at room temperature to obtain a mixed solution. Take 5g of expanded graphite worm powder and add it to the mixed solution, and stir the mixture at room temperature for 10h, and dry it at 90℃ for 10h to obtain a mixed sample powder. The obtained mixed sample powder is placed in an argon environment and calcined at 500℃ for 4h to obtain a calcined product.
[0064] 3) 0.3 g of the calcined product was placed in a fixed bed reactor. Before the reaction, pure H2 was introduced for reduction at 400°C for 2 h at a reducing gas flow rate of 50 mL / min to obtain expanded graphite worm powder-loaded Cu-In-Fe trimetallic catalyst (Cu-In-Fe / EG);
[0065] 4) After reduction, acetylene mixed gas was introduced at a rate of 50 mL / min. The volume concentration of the acetylene mixed gas was: 0.33% acetylene, 6.6% hydrogen, 33% ethylene, and the balance nitrogen, with a total amount of 100%. -1 The hydrogenation reaction was carried out at 0.1 MPa, pressure and 150°C. The peak areas of ethane, ethylene, acetylene and C4 were detected online by gas chromatography, and the conversion rate of acetylene and its selectivity for ethylene were calculated by area normalization method.
[0066] Calculation based on chromatographic data showed that when the reaction reached stability, the acetylene conversion was 99.9% and the ethylene selectivity was 99.1%. After 300 hours of reaction, the acetylene conversion was 98.8% and the ethylene selectivity was 98.2%.
[0067] Comparative Example 3
[0068] 1) Add 10g of graphite and 100g of concentrated sulfuric acid to a beaker, mix, and stir at room temperature for 10h to obtain a mixture. Add 70g of potassium persulfate to the mixture, stir evenly, and immediately move into an 80°C water bath for 5min to obtain acidic expanded graphite. Filter the obtained acidic expanded graphite in a vacuum, wash to neutrality, and dry at 60°C for 5h to obtain expanded graphite worm powder (EG).
[0069] 2) Weigh 0.295g of anhydrous copper nitrate, 0.131g of indium nitrate and 0.217g of ferric nitrate and dissolve them in deionized water, and stir them thoroughly at room temperature to obtain a mixed solution. Take 5g of expanded graphite worm powder and add it to the mixed solution, and stir the mixture at room temperature for 10h, and dry it at 90℃ for 10h to obtain a mixed sample powder. The obtained mixed sample powder is placed in an argon environment and calcined at 500℃ for 4h to obtain a calcined product.
[0070] 3) 0.3 g of the calcined product was placed in a fixed bed reactor. Before the reaction, pure H2 was introduced for reduction at 400°C for 2 h at a reducing gas flow rate of 50 mL / min to obtain expanded graphite worm powder-loaded Cu-In-Fe trimetallic catalyst (Cu-In-Fe / EG);
[0071] 4) After reduction, acetylene mixed gas was introduced at a rate of 50 mL / min. The volume concentration of the acetylene mixed gas was: 0.33% acetylene, 6.6% hydrogen, 33% ethylene, and the balance nitrogen, with a total amount of 100%. -1 The hydrogenation reaction was carried out at 0.1 MPa, pressure and 150°C. The peak areas of ethane, ethylene, acetylene and C4 were detected online by gas chromatography, and the conversion rate of acetylene and its selectivity for ethylene were calculated by area normalization method.
[0072] Calculation based on chromatographic data showed that when the reaction reached stability, the acetylene conversion was 90.3% and the ethylene selectivity was 88.9%. After 100 hours of reaction, the acetylene conversion was 73.8% and the ethylene selectivity was 70.9%.
[0073] Through Example 2 and Comparative Example 3, it can be seen that the ratio of graphite to concentrated sulfuric acid will affect the prepared expanded graphite worm powder as a carrier, thereby affecting the performance of the catalyst of the present invention.
[0074] Example 3
[0075] 1) Add 10g of graphite and 500g of concentrated sulfuric acid to a beaker, mix, and stir at room temperature for 10h to obtain a mixture. Add 70g of potassium persulfate to the mixture, stir evenly, and immediately move into an 80°C water bath for 5min to obtain acidic expanded graphite. Filter the obtained acidic expanded graphite in a vacuum, wash it to neutrality, and dry it at 80°C for 5h to obtain expanded graphite worm powder (EG).
[0076] 2) Weigh 0.251g of anhydrous copper sulfate, 0.113g of indium sulfate and 0.179g of ferric sulfate and dissolve them in deionized water, and stir them thoroughly at room temperature to obtain a mixed solution. Take 5g of expanded graphite worm powder and add it to the mixed solution, and stir the mixture at room temperature for 8h, and dry it at 90℃ for 10h to obtain a mixed sample powder. The obtained mixed sample powder is placed in an argon environment and calcined at 400℃ for 4h to obtain a calcined product.
[0077] 3) 0.3 g of the calcined product was placed in a fixed bed reactor. Before the reaction, pure H2 was introduced for reduction at 400°C for 2 h at a reducing gas flow rate of 50 mL / min to obtain expanded graphite worm powder-loaded Cu-In-Fe trimetallic catalyst (Cu-In-Fe / EG);
[0078] 4) After reduction, acetylene mixed gas was introduced at a rate of 50 mL / min. The volume concentration of the acetylene mixed gas was: 0.33% acetylene, 3.3% hydrogen, 33% ethylene, and the balance nitrogen, with a total amount of 100%. -1 The hydrogenation reaction was carried out at 0.1 MPa, pressure and 160°C. The peak areas of ethane, ethylene, acetylene and C4 were detected online by gas chromatography, and the conversion rate of acetylene and its selectivity for ethylene were calculated by area normalization method.
[0079] Calculation based on chromatographic data showed that when the reaction reached stability, the acetylene conversion was 99.5% and the ethylene selectivity was 98.9%. After 400 hours of reaction, the acetylene conversion was 98.1% and the ethylene selectivity was 97.1%.
[0080] Comparative Example 4
[0081] 1) Add 10g of graphite and 500g of concentrated sulfuric acid to a beaker, mix, and stir at room temperature for 10h to obtain a mixture. Add 70g of potassium persulfate to the mixture, stir evenly, and immediately move into an 80°C water bath for 5min to obtain acidic expanded graphite. Filter the obtained acidic expanded graphite in a vacuum, wash it to neutrality, and dry it at 80°C for 5h to obtain expanded graphite worm powder (EG).
[0082] 2) Weigh 0.251 g of anhydrous copper sulfate and dissolve it in deionized water, and stir it thoroughly at room temperature to obtain a mixed solution. Take 5 g of expanded graphite worm powder and add it to the mixed solution, and stir the mixture at room temperature for 8 hours, and dry it at 90°C for 10 hours to obtain a mixed sample powder. The obtained mixed sample powder is placed in an argon environment and calcined at 400°C for 4 hours to obtain a calcined product.
[0083] 3) 0.3 g of the calcined product was placed in a fixed bed reactor. Before the reaction, pure H2 was introduced for reduction at 400°C for 2 h at a reducing gas flow rate of 50 mL / min to obtain an expanded graphite worm powder-supported Cu catalyst (Cu / EG);
[0084] 4) After reduction, acetylene mixed gas was introduced at a rate of 50 mL / min. The volume concentration of the acetylene mixed gas was: 0.33% acetylene, 3.3% hydrogen, 33% ethylene, and the balance nitrogen, with a total amount of 100%. -1The hydrogenation reaction was carried out at 0.1 MPa, pressure and 160°C. The peak areas of ethane, ethylene, acetylene and C4 were detected online by gas chromatography, and the conversion rate of acetylene and its selectivity for ethylene were calculated by area normalization method.
[0085] Calculation based on chromatographic data showed that when the reaction reached stability, the acetylene conversion was 77.5% and the ethylene selectivity was 52.3%. After 50 hours of reaction, the acetylene conversion was 61.1% and the ethylene selectivity was 47.1%.
[0086] Comparative Example 5
[0087] 1) Add 10g of graphite and 500g of concentrated sulfuric acid to a beaker, mix, and stir at room temperature for 10h to obtain a mixture. Add 70g of potassium persulfate to the mixture, stir evenly, and immediately move into an 80°C water bath for 5min to obtain acidic expanded graphite. Filter the obtained acidic expanded graphite in a vacuum, wash it to neutrality, and dry it at 80°C for 5h to obtain expanded graphite worm powder (EG).
[0088] 2) Weigh 0.113 g of indium sulfate and dissolve it in deionized water, and stir it thoroughly at room temperature to obtain a mixed solution. Take 5 g of expanded graphite worm powder and add it to the mixed solution, and stir the mixture at room temperature for 8 hours, and dry it at 90°C for 10 hours to obtain a mixed sample powder. The obtained mixed sample powder is placed in an argon environment and calcined at 400°C for 4 hours to obtain a calcined product.
[0089] 3) 0.3 g of the calcined product was placed in a fixed bed reactor. Before the reaction, pure H2 was introduced for reduction at 400°C for 2 h with a reducing gas flow rate of 50 mL / min to obtain an expanded graphite worm powder-loaded In catalyst (In / EG);
[0090] 4) After reduction, acetylene mixed gas was introduced at a rate of 50 mL / min. The volume concentration of the acetylene mixed gas was: 0.33% acetylene, 3.3% hydrogen, 33% ethylene, and the balance nitrogen, with a total amount of 100%. -1 The hydrogenation reaction was carried out at 0.1 MPa, pressure and 160°C. The peak areas of ethane, ethylene, acetylene and C4 were detected online by gas chromatography, and the conversion rate of acetylene and its selectivity for ethylene were calculated by area normalization method.
[0091] Calculation based on chromatographic data showed that when the reaction reached stability, the acetylene conversion was 27.5% and the ethylene selectivity was 22.3%. After 15 hours of reaction, the acetylene conversion was 22.1% and the ethylene selectivity was 17.5%.
[0092] Comparative Example 6
[0093] 1) Add 10g of graphite and 500g of concentrated sulfuric acid to a beaker, mix, and stir at room temperature for 10h to obtain a mixture. Add 70g of potassium persulfate to the mixture, stir evenly, and immediately move into an 80°C water bath for 5min to obtain acidic expanded graphite. Filter the obtained acidic expanded graphite in a vacuum, wash it to neutrality, and dry it at 80°C for 5h to obtain expanded graphite worm powder (EG).
[0094] 2) Weigh 0.179 g of ferric sulfate and dissolve it in deionized water, and stir it thoroughly at room temperature to obtain a mixed solution. Take 5 g of expanded graphite worm powder and add it to the mixed solution, and stir the mixture at room temperature for 8 hours, and dry it at 90°C for 10 hours to obtain a mixed sample powder. The obtained mixed sample powder is placed in an argon environment and calcined at 400°C for 4 hours to obtain a calcined product.
[0095] 3) 0.3 g of the calcined product was placed in a fixed bed reactor. Before the reaction, pure H2 was introduced for reduction at 400°C for 2 h at a reducing gas flow rate of 50 mL / min to obtain an expanded graphite worm powder-supported Fe catalyst (Fe / EG);
[0096] 4) After reduction, acetylene mixed gas was introduced at a rate of 50 mL / min. The volume concentration of the acetylene mixed gas was: 0.33% acetylene, 3.3% hydrogen, 33% ethylene, and the balance nitrogen, with a total amount of 100%. -1 The hydrogenation reaction was carried out at 0.1 MPa, pressure and 160°C. The peak areas of ethane, ethylene, acetylene and C4 were detected online by gas chromatography, and the conversion rate of acetylene and its selectivity for ethylene were calculated by area normalization method.
[0097] Calculation based on chromatographic data showed that when the reaction reached stability, the acetylene conversion was 19.5% and the ethylene selectivity was 34.3%. After 15 hours of reaction, the acetylene conversion was 11.6% and the ethylene selectivity was 26.5%.
[0098] Through Example 3 and Comparative Examples 4-6, it can be seen that the Cu-In-Fe trimetallic catalyst of the present invention is indeed superior to the Cu, In, Fe single metal catalysts.
Claims
1. An expanded graphite worm powder loaded Cu-In-Fe trimetallic catalyst, characterized in that: The catalyst is prepared by using expanded graphite worm powder as a carrier by the following method: copper salt, indium salt and iron salt are loaded onto expanded graphite worm powder by wet impregnation to obtain a mixed sample, and then the mixed sample is placed in an inert gas environment and calcined at high temperature to obtain a calcined product; and then the obtained calcined product is reduced in a hydrogen atmosphere to obtain an expanded graphite worm powder loaded Cu-In-Fe trimetallic catalyst; Among them, the feeding ratio of the copper salt, indium salt, iron salt and expanded graphite worm powder needs to make the expanded graphite worm powder load the Cu-In-Fe trimetallic catalyst with 1%-10% of the theoretical loading amount of copper, 0.1%-5% of indium, and 0.1%-2.5% of iron. The theoretical loading amount is calculated as the percentage of the mass of copper, indium and iron elements contained in the copper salt, indium salt and iron salt respectively to the mass of the expanded graphite worm powder.
2. The expanded graphite worm powder loaded Cu-In-Fe trimetallic catalyst as claimed in claim 1, characterized in that: The theoretical loading amount of copper is 1%-5%, the theoretical loading amount of indium is 0.5%-2.5%, and the theoretical loading amount of iron is 0.5%-2%.
3. The expanded graphite worm powder loaded Cu-In-Fe trimetallic catalyst as claimed in claim 1, characterized in that: The calcination temperature is 150-1200°C, more preferably 250-1000°C, and further preferably 350-700°C; the calcination time is 1-8h, and more preferably 2-6h.
4. The expanded graphite worm powder loaded Cu-In-Fe trimetallic catalyst as claimed in claim 1, characterized in that: The reduction temperature is 200-600°C, more preferably 350-450°C; the reduction time is 1-4h.
5. A method for preparing a Cu-In-Fe trimetallic catalyst loaded with expanded graphite worm powder as claimed in any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) Weigh copper salt, indium salt and iron salt, dissolve them in deionized water, and stir them thoroughly at room temperature to obtain a mixed solution; add expanded graphite worm powder to the mixed solution, stir the mixture at room temperature for 8-12 hours, and dry it to obtain a mixed sample powder; (2) placing the mixed sample powder obtained in step (1) in an inert gas environment and calcining it at high temperature to obtain a calcined product; (3) reducing the calcined product obtained in step (2) in a hydrogen atmosphere to obtain a Cu-In-Fe trimetallic catalyst supported by expanded graphite worm powder.
6. The preparation method according to claim 5, characterized in that: The preparation method of the expanded graphite worm powder comprises the following steps: (a) adding graphite and an appropriate amount of concentrated sulfuric acid into a beaker, mixing, stirring at room temperature for ≥2h to obtain a mixture, adding potassium persulfate to the mixture, stirring evenly, and immediately moving into a water bath to obtain acidic expanded graphite; wherein, by mass, the graphite: potassium persulfate: concentrated sulfuric acid = 1:5-10:40-100, preferably 1:5-10:45-55; (b) filtering the acidic expanded graphite obtained in step (1), washing it to neutrality, and drying it in vacuum to obtain expanded graphite worm powder.
7. The preparation method according to claim 6, characterized in that: The water bath temperature of step (a) is 40-120° C., more preferably 60-100° C., and the water bath time is 1-20 min.
8. Use of the expanded graphite worm powder loaded with Cu-In-Fe trimetallic catalyst as claimed in any one of claims 1 to 4 in the semi-hydrogenation reaction of acetylene.
9. The use according to claim 8, characterized in that: The acetylene semi-hydrogenation reaction is specifically carried out as follows: a raw material gas containing acetylene and hydrogen is introduced into a fixed bed reactor filled with expanded graphite worm powder loaded with a Cu-In-Fe trimetallic catalyst to convert acetylene into ethylene.
10. The use according to claim 9, characterized in that: The reaction conditions of acetylene semi-hydrogenation are: reaction temperature 80-250°C, reaction pressure 0.1MPa.
Citation Information
Patent Citations
Catalyst and application as well as preparation method thereof
CN103301838A
Doped copper-iron-molybdenum catalyst as well as preparation method and application thereof
CN116764643A
Composite Hf-containing carrier material loaded CuO catalyst and preparation and application thereof in acetylene hydrogenation reaction
CN117225413A
Surface modifying method of natural graphite by carbonnanofiber
KR1020080006899A
Hydrogenation of gasolines
US3051647A